2012
DOI: 10.1038/nature10934
|View full text |Cite
|
Sign up to set email alerts
|

Electron tomography at 2.4-ångström resolution

Abstract: Transmission electron microscopy is a powerful imaging tool that has found broad application in materials science, nanoscience and biology. With the introduction of aberration-corrected electron lenses, both the spatial resolution and the image quality in transmission electron microscopy have been significantly improved and resolution below 0.5 ångströms has been demonstrated. To reveal the three-dimensional (3D) structure of thin samples, electron tomography is the method of choice, with cubic-nanometre resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
337
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(359 citation statements)
references
References 36 publications
4
337
0
6
Order By: Relevance
“…Laboratory investigations have shown that gold [50,51] and silver [33] nanoparticles aggregate by a similar process of self-assembly to make fractal dendrites. In particular, the nanoparticles' aggregation is governed by a kinetically driven process called diffusion-limited aggregation (DLA) [33,51,52], which results in characteristic tree-like dendrites with similar fractal dimensions. Saunders and Schoenly [14,34] showed that dendrites in epithermal ores had similar fractal dimensions to those produced in the lab by gold nanoparticle aggregation, and they proposed that a modified DLA produced the natural fractal dendrites from the Sleeper deposit.…”
Section: Aggregation Of Metallic Nanoparticlesmentioning
confidence: 99%
“…Laboratory investigations have shown that gold [50,51] and silver [33] nanoparticles aggregate by a similar process of self-assembly to make fractal dendrites. In particular, the nanoparticles' aggregation is governed by a kinetically driven process called diffusion-limited aggregation (DLA) [33,51,52], which results in characteristic tree-like dendrites with similar fractal dimensions. Saunders and Schoenly [14,34] showed that dendrites in epithermal ores had similar fractal dimensions to those produced in the lab by gold nanoparticle aggregation, and they proposed that a modified DLA produced the natural fractal dendrites from the Sleeper deposit.…”
Section: Aggregation Of Metallic Nanoparticlesmentioning
confidence: 99%
“…Finally, one advantage of WBP and SIRT are their easier implementation and use, whereas TVM and DART are sensitive to the reconstruction parameters and require expert knowledge for properly setting regularization parameters or ratio of boundary pixels, respectively. In summary, to determine which of the many possible reconstruction approaches, such as WBP [13], SIRT [26], TVM [23], DART [22], ART [27], EST [60], Directt [61], W-SIRT [62], is best for a particular class of samples, a study as the one presented here for tubular domains in a slab matrix should be carried out. 1 …”
Section: Discussionmentioning
confidence: 99%
“…Equal results have been obtained more quickly by using a centre of mass approach [270] in combination with the fact that the specimen here is isolated and that its support χ(x, y, z)…”
Section: Details: Tomographic Reconstructionmentioning
confidence: 99%